Partial Hemiresurfacing of Osteochondral Defects of the Talus? Surgical Technique and Preliminary Report from Four Patients - Beck, Sascha; Busch, André; Zilkens, Christoph; Warwas, Sebastian; Jäger, Marcus (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
Background: Osteochondral lesions of the medial talus (OLT) frequently lead to chronic ankle pain and osteoarthritis. Arthroscopic debridement, subchondral bone stimulation by drilling, and microfracturing are options for primary therapy in small lesions. In larger lesions, restoration of the talar dome contour seems to be a mandatory course of action.Methods: In a case series, we followed up four patients being treated with a focal resurfacing prosthetic due to large osteochondral talar lesions. In contrast to other studies, we can report on an off-label application to restore defects of the lateral talar dome with two patients for the first time. At follow-up, three patients reported a remarkable reduction in pain and were able to return to sports activities. One patient developed pseudarthrosis of the medial malleolar osteosynthesis.Conclusions: With selected patients, focal resurfacing appears to be an option for large osteochondral defects of the talus.
Keywords: talus; osteochondral lesion; resurfacing; implant; ankle